A First Course in Statistics / Third Edition - Dietrich Frank H. Ii; Mcclave James T (Dellen Publishing Company, 1991)
What is Statistics?, Methods for Describing Sets of Data, Probability, Random Variables and Probability Distributions, Sampling Distributions, Estimation and Tests of Hypotheses: Single Sample, Comparing Two or More Population Means, Comparing Two or More Population Proportions, Simple Linear Regression, Appendices, Index.